Reproductive isolation between Salvia elegans and S. fulgens, two hummingbird‐pollinated sympatric sages. (31st August 2018) - Cuevas, E.; Espino, J.; Marques, I.
Abstract: The integrity of species in sympatric contact sites is dependent on the existence of reproductive isolating mechanisms, which restrict gene flow between them. However, we know little about the mechanisms that enable the coexistence of species with similar floral morphologies. Here, we evaluated several reproductive isolation barriers between Salvia elegans and S. fulgens, two sympatric sages with a similar ornithophilous floral syndrome, offering nectar as the main reward. Over 3 years, we evaluated broad‐scale geographic isolation, floral phenologies and floral visitors as pre‐pollination barriers, and fruit set, seed number and seed germination as post‐pollination barriers. We found considerable geographic isolation and significant altitudinal differences between the two sages. The flowering period of both sages always overlapped extensively during the 3 years of this study, but hummingbirds were highly specific, visiting one or the other Salvia species and showing aggressive territorial behaviour. Interspecific experimental crosses revealed that hybrid seeds might be formed although strong asymmetric barriers were found depending on the species acting as the maternal donor. Despite the low level of flowering asynchrony, reproductive isolation was remarkably high in the two sages. Geographic isolation and pollinator fidelity were the main factors responsible for maintaining species integrity. Despite an extensive review, we found very few studies quantifying the efficiency of isolation barriers in Neotropical plants or even the importance of hummingbirds as pollinators.